The Politeness/Impoliteness Divide English-Based Theories and Speech Acts Practice in Moroccan Arabic - Anssari-Naim, Saida (English In The World Series, 2016)
This book aims to explore the contribution that Moroccan Arabic and the cultural code associated with this language makes to the theoreti¬cal discourse on politeness. Lt focuses on the way in which significant speech acts such as expressing gratitude, invitations and compliments are managed. Politeness is a strategy to preserve community values and to construct personal iden¬tities related to these values. El objetivo de este libro es explorar la contribución del árabe marroquí y del código cultural asociado con esta lengua al discurso teórico sobre la cortesía. Se centra en el modo en el que se manejan los actos de habla significativos como la expresión de gratitud, las invitaciones y los cumplidos. La cortesía se revela como una estrategia para preservar los valores de la comunidad y para construir las identidades personales relacionadas con estos valores.